Enzootic bovine leucosis in dairy cows in Greece - ΔΗΜΗΤΡΙΑΔΗΣ, Ι. Α.; ΣΕΪΤΑΡΙΔΗΣ, Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
658 sera from dairy cows belonging to 43 herds with imported or non imported animals of above two years old, were examined by using the Ouchterlony' s immunodiffusion method. Fifteen sera (2,2%) from animals of two herds (4,6%) had specific antibodies (precipitins) against the Enzootic Bovine Leucosis. No one among 419 sera from cattle of herds with non imported animals was found positive to Enzootic Bovine Leucosis while 15 out of 239 sera from cattle of 7 herds with imported or born from imported animals were found positive to this disease that is 6,3% of sera and 28,5% of herds. The antigen, the positive reference serum and the agar gel used were kindly supplied by Behringwerke A.G. to which we express our gratituude.